The effect of credit composition on entrepreneurship - Ali Nassiri Aghdam; Shahin Behdarvand; Mohammad Ghasemi Sheshdeh (Latin American Journal of Central Banking (LAJCB), 2023)
In this study, we aim to assess the relevance of credit composition to entrepreneurship empirically in light of the Schumpeterian perspective. The results of such an analysis can imply whether central banks should continue with the so-called neutrality principle or undertake an active credit policy. We employ a panel data model to quantify the effect of credit composition on entrepreneurship in 54 high- and middle-income economies from 2001 to 2016. To capture credit composition, we disaggregate total credit as credit to non-financial and financial businesses as well as credit to households and mortgages, and we hypothesize that the larger share of credit for non-financial businesses and households would be associated with greater entrepreneurship. The results indicate that credit composition is important for both high- and middle-income economies, but the effective composition of credit is different in the two sub-samples, which is why the effectiveness of credit allocation should not be taken for granted and active remedies are required. This paper corroborates the Schumpeterian view on the ties between credit allocation and entrepreneurship in both high- and middle-income economies.
Keywords: C23; E42; E50; G20; L26; 330; Entrepreneurship; Credit guidance; Credit composition; Credit to non-financial businesses; Panel data